On Fučík type spectrum for problem with integral nonlocal boundary condition - Sergejeva, Natalija; Pečiulytė, Sigita (Nonlinear Analysis: Modelling and Control, 2019)
The Fučík equation x' '= -μ x+λ x- with two types of nonlocal boundary value conditions are considered. The Fučík type spectrum for both problems are constructed. The visualization of the spectrum for some values of parameter γ is provided.
Keywords: Fučik type problem; Fučik spectrum; integral nonlocal condition